Maternal hostility, moral reasoning and sharing in children - Er-Vargün, Gamze; Akgün, Serap (Springer, 2024)
Maternal hostility is a risk factor for children’s prosocial behavior. However, the mediating mechanisms underlying the relation between maternal hostility and children’s sharing behavior remain unknown. The present study primarily aimed to examine the relations among moral reasoning, maternal hostility, and sharing behavior during early and middle childhood. The sample consisted of 206 children (91 boys, 115 girls) aged between 4 and 9 years old (M = 84.27 (month), SD = 16.86) living in Turkey. Children’s sharing behavior was measured by the number of stickers they gave to other children in the dictator game. Children’s moral reasoning abilities were evaluated with several questions asked after reading four stories containing moral violations. Lastly, children’s perceptions of hostile behaviors of their mothers were evaluated with the Child-Puppet Interview. The results of the mediation analysis conducted with structural equation modeling showed that the relationship between maternal hostility and children’s sharing behavior was fully mediated by children’s moral reasoning abilities. Maternal hostility was negatively related to children’s moral reasoning, and children’s moral reasoning was found to be positively linked with sharing. The findings showed that hostile behaviors of mothers towards their children impaired children’s moral reasoning abilities and, in turn, decreased sharing. © The Author(s), under exclusive licence to Springer Science+Business Media, LLC, part of Springer Nature 2023.
Keywords: Children; Maternal hostility; Moral reasoning; Sharing